Emotional intelligence as a moderator of the relationship between occupational stress characteristics and job satisfaction - Yao, Amy Chu Jiang (Universiti Malaysia Sarawak (UNIMAS), 2008)
This study was conducted to examine the moderating role of emotional intelligence (EI) in the relationship between occupational stress characteristics and job satisfaction. Implications of the study on job street theories of practice, research methodologies, conceptual limitations, and suggested directions for future research are also discussed.